Structural Insights into the Incorporation of the Mo Cofactor into Sulfite Oxidase from Site‐Directed Spin Labeling. Issue 40 (18th August 2015) - Hahn, Aaron; Engelhard, Christopher; Reschke, Stefan; Teutloff, Christian; Bittl, Robert; Leimkühler, Silke; Risse, Thomas
Abstract Mononuclear molybdoenzymes catalyze a broad range of redox reactions and are highly conserved in all kingdoms of life. This study addresses the question of how the Mo cofactor (Moco) is incorporated into the apo form of human sulfite oxidase (hSO) by using site‐directed spin labeling to determine intramolecular distances in the nanometer range. Comparative measurements of the holo and apo forms of hSO enabled the localization of the corresponding structural changes, which are localized to a short loop (residues 263–273) of the Moco‐containing domain. A flap‐like movement of the loop provides access to the Moco binding‐pocket in the apo form of the protein and explains the earlier studies on the in vitro reconstitution of apo‐hSO with Moco. Remarkably, the loop motif can be found in a variety of structurally similar molybdoenzymes among various organisms, thus suggesting a common mechanism of Moco incorporation.